The Application of School Watching Method to Increase the Earthquake Disaster Knowledge of Primary School Students - Sri Adelila Sari; Husnul Khatimah (Journal of Education and Learning (EduLearn), 2015)
The study entitled "The Application of School Watching to Increase the Earthquake Disaster Knowledge of Primary School Students, MIN Blang Mancung, Aceh" was aimed to describe the students' knowledge of the different dangerous objects in the face of an earthquake. The approach used in this study was qualitative and quantitative. The type of study was descriptive. Subjects used were as many as 30 students MIN Blang Mancung, Aceh. The method used was an experimental, which was divided into two classes, namely the experimental and control classes. Data collection technique was using questionnaires, which included the questions about common dangerous objects, dangerous objects in the class and also in the school yard. The results showed that there was a significant effect on students' knowledge before and after the implementation of the method School Watching. In addition, the knowledge of students toward the dangerous objects was found to be significant different between control and experimental class.